2020
DOI: 10.1016/j.omtn.2020.08.006
|View full text |Cite
|
Sign up to set email alerts
|

STAT3-Induced lncRNA SNHG17 Exerts Oncogenic Effects on Ovarian Cancer through Regulating CDK6

Abstract: Emerging studies indicate that long noncoding RNAs (lncRNAs) play crucial roles in ovarian cancer (OC). By analyzing high-throughput data, we found that SNHG17 was highly expressed in multiple OC cohorts. However, its functions in OC were not explored. In this study, lncRNA expression in OC was analyzed by a series of microarray data. The functions of SNHG17 were investigated by various in vitro and in vivo assays. Fluorescence in situ hybrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 38 publications
1
29
0
Order By: Relevance
“…Due to their ability to interact with different structures and molecules, lncRNAs have high heterogeneity and functional diversity [ 25 27 ]. As demonstrated previously, lncRNAs function importantly in regulating the cell fate determination, disease occurrence, and tumor progression [ 28 31 ]. Thus, this study focused on exploring the regulatory role of NORAD (also known as LINC00657) [ 32 ] in the stemness of PCSCs.…”
Section: Discussionmentioning
confidence: 83%
“…Due to their ability to interact with different structures and molecules, lncRNAs have high heterogeneity and functional diversity [ 25 27 ]. As demonstrated previously, lncRNAs function importantly in regulating the cell fate determination, disease occurrence, and tumor progression [ 28 31 ]. Thus, this study focused on exploring the regulatory role of NORAD (also known as LINC00657) [ 32 ] in the stemness of PCSCs.…”
Section: Discussionmentioning
confidence: 83%
“…Among the overlapping three target genes, STAT3 is the most widely studied. STAT3, that is signal transducer and activator of transcription factor 3, relates not only to the proliferation, invasion, metastasis, apoptosis of ovarian cancer cells, but also chemotherapy resistance (Zhong et al 2021;Liu et al 2021;Pan et al 2020). BUB1 (budding uninhibited by benzimidazole 1) is a mitotic checkpoint protein that is overexpressed in various types of cancer, including breast cancer, gastric cancer, pancreatic cancer and so on (Han et al 2015;Piao et al 2019;Bai et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Our study subsequently indicated that STAT3 was the transcription factor for LINC00504. STAT3 serves as the transcription factor for lncRNA SNHG17 [22]. Moreover, STAT3 also plays an important role in TNBC.…”
Section: Discussionmentioning
confidence: 99%